2016
DOI: 10.1021/jacs.6b02470
|View full text |Cite
|
Sign up to set email alerts
|

An NAD(P)H-Dependent Artificial Transfer Hydrogenase for Multienzymatic Cascades

Abstract: Enzymes typically depend on either NAD(P)H or FADH 2 as hydride source for reduction purposes. In contrast, organometallic catalysts most often rely on isopropanol or formate to generate the reactive hydride moiety. Here we show that incorporation of a Cp*Ir cofactor possessing a biotin moiety and 4,7-dihydroxy-1,10-phenanthroline into streptavidin (Sav) yields an NAD(P)H-dependent artificial transfer hydrogenase (ATHase). This ATHase (0.1 mol%) catalyzes imine reduction with 1 mM NADPH (2 mol%), which can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 67 publications
0
63
0
Order By: Relevance
“…They combined an iridium-containing organometallic transfer-hydrogenation catalyst with, for example, a monoamine oxidase and a catalase for the reduction of imines and demonstrated deracemization of cyclic amines. Recently, they investigated an NAD(P)H-dependent artificial transfer hydrogenase and combined it in a multi-enzymatic cascade, again for the synthesis of chiral secondary amines 66 . Moreover, it was possible to tune their artificial transfer hydrogenase for the regeneration of nicotinamide mimics, which was combined with an enoate reductase to synthesize chiral maleimides 67 .…”
mentioning
confidence: 99%
“…They combined an iridium-containing organometallic transfer-hydrogenation catalyst with, for example, a monoamine oxidase and a catalase for the reduction of imines and demonstrated deracemization of cyclic amines. Recently, they investigated an NAD(P)H-dependent artificial transfer hydrogenase and combined it in a multi-enzymatic cascade, again for the synthesis of chiral secondary amines 66 . Moreover, it was possible to tune their artificial transfer hydrogenase for the regeneration of nicotinamide mimics, which was combined with an enoate reductase to synthesize chiral maleimides 67 .…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Our group recently demonstrated that such ArMs improve the bio-compatibility of the organometallic cofactor, the protein host providing protection against deactivation, allowing their integration into cascades with natural enzymes. [10][11][12] In abiomimetic spirit, we surmised that the activity of an anchored catalyst precursor might be upregulated by the action of an external trigger,i deally an atural enzyme,a t aremote position in the host protein. Such systems could form the basis of more elaborate cross-regulated enzyme cascades whereby the product of the ArM-catalyzed reaction inhibits the activating enzyme.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18] In the context of upregulation, we hypothesized that abiotinylated Cp*M moiety (M = Rh III ,Ir III )might prove versatile as 1) the [Cp* biot MCl 2 ] 2 precursor (or in combination with wild-type streptavidin, WT Sav hereafter) shows limited catalytic activity,both for CÀHactivation (M = Rh III )and for imine reduction (M = Rh III or Ir III ); [19][20][21] 2) addition of as uitable ligand (e.g.a midoamines,d erived from natural amino acids) leads to significant rate acceleration for the transfer hydrogenation of imines and ketones; [19][20][21][22] and 3) embedding aCp*Ir moiety within Sav shields the cofactor from inhibition by other proteins,e nabling enzyme cascades. [10][11][12] In the context of ligand-accelerated catalysis, [23] Hilvert et al screened alibrary of tripeptides to identify ligands that accelerate the [Cp*IrL 3 ]-catalyzed transfer hydrogenation (L = Cl À or H 2 O). They identified glycine-glycine-phenylalanine (GGF hereafter) as the tripeptide yielding the most active complex in combination with [Cp*IrCl 2 ] 2 .…”
mentioning
confidence: 99%
“…Mechanistically,i th as been establishedt hat NADH or formate reacts with organoiridium complexes to generate iridium-hydride species that are capable of transferring its hydride to protons, [81] dioxygen, [82,83] or organic electrophiles [84,85] (Scheme 4). This chemistryi se xtraordinarily versatile, as exemplified by its use in applicationss uch as biocatalytic cascade processes (Ward and co-workers) [86,87] or methods for reductive alkylation of proteins (Francisand co-worker). [88] Transfer hydrogenation is an attractive target for further SIMCat-promoted chemistryd evelopment.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%